"Good, better, creative": the influence of creativity on goal scoring in elite soccer. Issue 21 (2nd November 2018) - Kempe, Matthias; Memmert, Daniel
ABSTRACT: This study investigated the level of creativity of goals scored in football. Therefore, all goals in the Football FIFA World Cup 2010 and 2014, as well as the Football UEFA Euro 2016 were qualitatively examined. Three Football experts evaluated the last eight actions before each goal using a creativity scale ranging from 0 to 10 (0 = not creative, 10 = highly creative) of all goals scored via open play (311 goals in 153 matches). Level of creativity was revealed using an Analysis of Variance and the frquency of high highly creative goals using a Kruskall- Wallis Test. The results showed that the closer the actions to a goal, the more creative they were evaluated. Teams that advanced to the later rounds of the tournament demonstrated greater creativity than teams that failed to do so. High creativity in the last two actions before the actual shot on goal proved to be the best predictor for game success. In conclusion, this study is the first one to show that creativity seems to be a factor for success in high level football. Thereby it provides an empirical basis for the ongoing debate on the importance of creativity training in football.